On the effect of water content on fatigue mechanical behaviors of mud-shale under stress disturbance conditions - Li, Xuguang; Wu, Jihuan; Yang, Haonan; Wang, Yu (Frontiers in Materials, 2023)
This work aims to reveal the fatigue mechanical behaviors of mud-shale subjected to multistage increasing-amplitude cyclic loads. The fatigue loading tests combined with real-time acoustic emission (AE) monitoring were employed to investigate the influence of water ratio on the deformation, damage, and fracture characteristics. Testing results show that rock fatigue life decreases with the increase of water content, and the hysteresis curve changes regularly with time. The failure process can be divided into three stages: initial stage, stable development stage and acceleration stage. The AE output activities were also influenced by the water content. The AE ring count and AE energy both decrease with increasing water ratio and the accumulative count and energy are the least for a sample having high water ratio. The AE activity shows a sudden increase trend at the amplitude-increasing moment, indicating the occurrence of strong damage within rock sample. The damage propagation within a cyclic loading stage is relatively small compared to the stress-increasing point. The results are helpful to understand the fatigue mechanical responses of water-sensitive soft work, as well as the slope stability of open-pit mine. The research results have important theoretical and practical significance for promoting slope treatment and disaster prevention.